Analisis Rekruitmen Politik: Studi Pada Rekruitmen Anggota Baru DPC PDI Perjuangan Kota Semarang Tahun 2012-2013 - Muhammad Agam Ashari; Budi Setiyono; Rina Martini (Journal of Politic and Government Studies, 2014)
ABSTRACTThis thesis entitled "Political Recruitment Analyse: Studies on New MemberRecruitment of DPC PDI Perjuangan Semarang Year 2012-2013". Compiled byMuhammad Agam Ashari, NIM: 14010110130113, Social Science Program andPolitical Science under the guidance of Setiyono Budi, S. Sos, M.Pol.Admin, Ph.D.,and Dra. Rina Martini, M.Sc.Political parties play an important role in the future leaders prints. It can besaid that good or bad depending on the quality of the party's leader in conducting therecruitment and education of members. PDI-Perjuangan is a big party and have abroad mass base. Greatness name PDI-Perjuangan penetrating through to areas suchas in Central Java, including in the city of Semarang. This is the background forresearchers to determine how the PDI-Perjuangan is able to obtain a high level ofelectability and also has many members.This study uses qualitative research methods with case studies. The studydesign used is the descriptive type of analytical data collection through interviewswith a number of informants that functionaries of PDI-Perjuangan cadres Semarangand examine any documents.Researchers analyzed all the phenomena of the background in the recruitmentprocess of the PDI-Perjuangan, including Sukarno heritages are attached to theChairman of the PDI-Perjuangan. PDI-Perjuangan does not implement a particularstrategy in recruiting members, that's a fact. Through this study the authors alsodescribe any factors supporting and inhibiting PDI perjuangan in recruit newmembers. Both of these factors would greatly affect the recruitment and imaging ofthe party as the “wong cilik” party's.PDI-Perjuangan should be more selective in recruiting members because ofperceived recruitment process is very important for future leaders prints. PDI-P isalso necessary to change the paradigm of the concept of leadership has MegawatiSoekarno breeds. Cadre too dependent on their leaders so that the leader decision isan absolute. Relationships like these could lead the party in these areas will feelstunted and do not have a voice to aspire.Keywords: Political Parties and the Recruitment System Absolute Loyalty